2021
DOI: 10.1186/s12941-021-00476-1
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of multidrug-resistant (MDR) Klebsiella pneumoniae harboring several β-lactamase and integron genes collected from several hospitals in the north of Iran

Abstract: Background Klebsiella pneumoniae is one of the leading causes of hospital outbreaks worldwide. Also, antibiotic-resistant K. pneumoniae is progressively being involved in invasive infections with high morbidity and mortality. The aim of the current study was to determine antimicrobial susceptibility patterns and the incidence of resistance genes (integron types and β-lactamase-encoded genes) among clinical isolates of K. pneumoniae. Methods In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 41 publications
3
15
1
1
Order By: Relevance
“…Meropenem had a 30% resistance rate, whereas imipenem and ertapenem both had a 31.3% resistance rate. This outcome was consistent with the research conducted by Farhadi et al [ 31 ], who observed that 33% of the K. pneumoniae isolates were resistant to imipenem. Furthermore, Pereira et al [ 32 ] found that 73 Klebsiella isolates found in samples of a urinary tract infection were extremely resistant to IMP.…”
Section: Discussionsupporting
confidence: 93%
“…Meropenem had a 30% resistance rate, whereas imipenem and ertapenem both had a 31.3% resistance rate. This outcome was consistent with the research conducted by Farhadi et al [ 31 ], who observed that 33% of the K. pneumoniae isolates were resistant to imipenem. Furthermore, Pereira et al [ 32 ] found that 73 Klebsiella isolates found in samples of a urinary tract infection were extremely resistant to IMP.…”
Section: Discussionsupporting
confidence: 93%
“…However, out of the 29 MDR isolates, only 10 (34.5%) were ESBL positive, and out of the 6 XDR isolates, only 3 (50%) were ESBL positive. The findings of this study reflect similar findings in similar studies performed elsewhere [22], [23], [24], [25]. However, we report that apart from possession of ESBL genes, which are known to confer resistance to bacterial organisms, there are other factors that are responsible to for drug resistance as observed in this study, which the present study could not determine.…”
Section: Discussionsupporting
confidence: 90%
“…Major (84.3%) K. pneumoniae isolates in our study were MDR with resistance to carbapenems for 45.7% isolates. Such high MDR rates were reported from China and Iran [30,31]. The prevalence of beta-lactamase genes bla CTX-M in our study was 74.2%, carbapenemase genes bla OXA-48 and bla NDM at 40.0% and 11.4%, respectively, similar to the prevalence of these genes published previously [31].…”
Section: Discussionsupporting
confidence: 90%
“…Such high MDR rates were reported from China and Iran [30,31]. The prevalence of beta-lactamase genes bla CTX-M in our study was 74.2%, carbapenemase genes bla OXA-48 and bla NDM at 40.0% and 11.4%, respectively, similar to the prevalence of these genes published previously [31]. Hypermucoviscous isolates identified in this study (n = 11) were attributed to ST23 K1 , ST86 K2 , ST23 K57 , ST65 K2 , and ST218 K57 genetic lines.…”
Section: Discussionmentioning
confidence: 56%